The assessment of socio-economic status: An alternative methodological and statistical approach - Μυλωνάς Κώστας; Ξανθοπούλου Χρυσάνθη (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF